Focusing on spontaneous coronary artery dissection: actuality and future perspectives - Buccheri, Dario; Zambelli, Giulia (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
Current ESC Guidelines on Acute Coronary Syndromes (ACS) declare that up to 20% of patients have no lesions or non-obstructive lesions of epicardial coronary arteries (1). When angiograms are silent, a spontaneous coronary artery dissection (SCAD) could be the underlying cause of myocardial ischemia.